2006
DOI: 10.1007/s10393-006-0065-1
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Borrelia burgdorferi-infection Prevalence of Nymphal Ixodes scapularis Ticks along Forest–Field Edges

Abstract: More than 19,000 human cases of Lyme disease (LD) are reported each year in the United States.Lyme disease cases occur when humans are exposed to the bacterium Borrelia burgdorferi through the bite of an infected ixodid tick. The probability of human exposure to infected ticks results from a combination of human behaviors and entomological risk. Human behaviors include use of tick habitats, use of protective clothing, and grooming for tick removal. Entomological risks include the density of ticks in a habitat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 25 publications
1
33
1
Order By: Relevance
“…Other host species may also be important, especially in influencing abundance of nymphal ticks, which transmit most B. burgdorferi infections to people. An analysis of six forest plots in southeastern New York State over 12 years supported positive correlations between plot-specific densities of nymphal ticks and prior densities of white-footed mice and eastern chipmunks (Ostfeld et al, 2006).…”
Section: Density Of Ixodes Scapularismentioning
confidence: 88%
See 2 more Smart Citations
“…Other host species may also be important, especially in influencing abundance of nymphal ticks, which transmit most B. burgdorferi infections to people. An analysis of six forest plots in southeastern New York State over 12 years supported positive correlations between plot-specific densities of nymphal ticks and prior densities of white-footed mice and eastern chipmunks (Ostfeld et al, 2006).…”
Section: Density Of Ixodes Scapularismentioning
confidence: 88%
“…Densities of adult ticks were positively correlated with those of deer pellet groups, a metric of deer density, at eight sites in southern Maine over 3 years (Rand et al, 2003). In other cases, however, spatial associations between deer and ticks have been weak (Schulze et al, 2001;Jordan and Schulze, 2005), nonexistent (Ostfeld et al, 2006), or even negative (Perkins et al, 2006). Other host species may also be important, especially in influencing abundance of nymphal ticks, which transmit most B. burgdorferi infections to people.…”
Section: Density Of Ixodes Scapularismentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, although climate works at large scales, topography, soil, and vegetation work at finer spatial ones (Thuiller et al, 2004a;Austin and Van Niel, 2011;Triviño et al, 2011;Barbet-Massin et al, 2012). A whole literature exists covering the role of landscape and land use in the performance of health-threatening arthropod vectors (i.e., Estrada-Peña, 2003;Diuk-Wasser et al, 2006;Horobik et al, 2006;Reiter and LaPointe, 2007;Vanwambeke et al, 2007Vanwambeke et al, , 2010, although they may have not reached the popularity or availability of bioclimatic covariates.…”
Section: The Choice Of Covariatesmentioning
confidence: 99%
“…Therefore, the ecotone between forested and open, vegetated areas supports populations of both white-tailed deer and white-footed mice (Despommier et al 2007). Horobik et al (2007) specifically examined disease transmission risk at the herbaceous-forest ecotone and concluded that, while the proportion of infected ticks and therefore entomological risk was higher in the forest interior, human activity at edges appears to be the driving factor that leads to increased incidence rates in areas with greater levels of herbaceous-forest edges.…”
Section: Introductionmentioning
confidence: 98%